EVALUASI PERLAKUAN AKUNTANSI ASET TETAP MENURUT PSAK NO. 16 PADA PT BANK MALUKU MALUT CABANG TOBELO - Ruata, Deisy Seleste; Tinangon, Jantje J.; Mawikere, Lidia M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The Bank is a financial institution whose main function is to raise funds from the community, and also provide services in the form of banking services. A bank in carrying out an operational activity always requires a variety of equipment, equipment, vehicles, and other means in terms of supporting activities carried out called fixed assets. This study aims to see how the accounting treatment of fixed assets, whether implemented in accordance with PSAK No. 16. Type of research used by the authors is qualitative data. Data source used is primary data. The method of analysis is descriptive method. The result of the research shows that PT Bank Maluku Malut Tobelo Branch in calculating depreciation using straight-line method of accounting treatment of fixed assets in terms of distribution, measurement, valuation, and presentation there is no problem at all applied by PT Bank Maluku Malut Tobelo Branch complies with the standard statement financial accounting No. 16.Keywords : Evaluation Treatment, Accounting, fixed assets,